A Cryptography-Based System for Offline Collection and Verification of Tax Revenue by County Governments in Kenya - Mandala, Nebert; Wanga, Carlton; Aduda, Josiah (European Scientific Journal, ESJ, 2017)
In the current setting of county governments in Kenya, efficient tax collection is highly dependent on validation of payment documents. This has led to challenges due to the fact that revenue collection has traditionally employed paper-based collection receipts. The research targets to address the challenges of validation of payment receipts in offline revenue collection systems. It supports automation attempts that have been made through the introduction of electronic mobile point of sale terminals. The solution is based on providing an offline model that supports the distributed nature of payment stations. This approach focuses on using cryptography-based techniques to enable offline validation of receipts even in cases of unreliable network connectivity. The objective is to provide a solution that affords ease of both revenue collections for the county governments and payments for the citizenry while stopping revenue leakages, ensuring reliable verification of payment receipts, thus maximising of revenue collection by providing reliable accounting reports. The research provides a reliable revenue collection system that enables offline receipting and verification of payment receipts in integrated mobile point of sale terminals. The solution presented has successfully been implemented and tested in one of the County Governments in Kenya.